The effect of reciting the Quran on the anxiety of neurosurgery Muslim candidates - Salari, Nader; Fayzi, Reza; Abdipuor, Elahe; Ghasemi, Hooman; Shohaimi, Shamarina; Mohammadi, Masoud (John Wiley and Sons, 2025)
Background: Anxiety is very common among patients undergoing surgery. Like other forms of surgery, neurosurgery can affect patients both physically and emotionally. One of the ways to control and reduce anxiety is to pay attention to spiritual interventions and spiritual health. The present study aimed to investigate the effect of the Qur'an on the anxiety of neurosurgery Muslim candidates. Methods: This study is interventional research with a pretest and posttest design with a control group. The research population included all patients who were candidates for brain and nerve surgery in the teaching-treatment hospitals in 2019. The samples were selected by probability and simple random sampling methods. The data collection tool included the Spielberger questionnaire and demographics (age, gender, marital status, education degree, job, etc.) and the vital signs checklist (blood pressure, heart rate, and respiration). Results: The results of this study showed that the sound of the Quran leads to a decrease in the level of anxiety in the experimental group. The effect size of the group for overt anxiety and anxiety subscales is 53.5% and 40%, respectively; blood pressure is 4.3%, breathing is 20.9%, and heart rate is 21.5%. Conclusion: Anxiety is an unpleasant complication that many people suffer from before various surgeries. The results of this study indicated that the sound of the Quran is a positive and effective factor in reducing anxiety before neurosurgery in Muslim patients who are candidates for this surgery, so health policymakers can use the results of this study as a research priority to reduce anxiety before surgery.